Effect of an integral quality monitor on 4‐, 6‐, 10‐MV, and 6‐MV flattening filter‐free photon beams. Issue 1 (3rd December 2020) - Nguyen, Trang Hong Thi; Yokoyama, Haruna; Kojima, Hironori; Isomura, Naoki; Takemura, Akihiro; Ueda, Shinichi; Noto, Kimiya
Abstract: Purpose: To investigate the effect of an integral quality monitor (IQM; iRT Systems GmbH, Koblenz, Germany) on 4, 6, 10, and 6‐MV flattening filter‐free (FFF) photon beams. Methods: We assessed surface dose, PDD20, 10, TPR20, 10, PDD curves, inline and crossline profiles, transmission factor, and output factor with and without the IQM. PDD, transmission factor, and output factor were measured for square fields of 3, 5, 10, 15, 20, 25, and 30 cm and profiles were performed for square fields of 3, 5, 10, 20, and 30 cm at 5‐, 10‐, and 30‐cm depth. Results: The differences in surface dose of all energies for square fields of 3, 5, 10, 15, 20, and 25 cm were within 3.7% whereas for a square field of 30 cm, they were 4.6%, 6.8%, 6.7%, and 8.7% for 4‐MV, 6‐MV, 6‐MV‐FFF, and 10‐MV, respectively. Differences in PDD20, 10, TPR20, 10, PDD, profiles, and output factors were within ±1%. Local and global gamma values (2%/2 mm) were below 1 for PDD beyond d max and inline/crossline profiles in the central beam region, respectively. The gamma passing rates (10% threshold) for PDD curves and profiles were above 95% at 2%/2 mm. The transmission factors for 4‐MV, 6‐MV, 6‐MV‐FFF, and 10‐MV for field sizes from 3 × 3 to 30 × 30 cm 2 were 0.926–0.933, 0.937–0.941, 0.937–0.939, and 0.949–0.953, respectively. Conclusions: The influence of the IQM on the beam quality (in particular 4‐MV X‐ray has not verified before) was tested and introduced a slight beam perturbation at the surface and build‐up region and the edge of the crossline/inline profiles. To use IQM in pre‐ and intra‐treatment quality assurance, a tray factor should be put into treatment planning systems for the dose calculation for the 4‐, 6‐, 10‐, and 6‐MV flattening filter‐free photon beams to compensate the beam attenuation of the IQM detector.